2023
DOI: 10.1111/dgd.12836
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic tetraspanin expression patterns mark various tissues during early Xenopus development

Abstract: The tetraspanins (Tspans) constitute a family of cell surface proteins with four transmembrane domains. Tspans have been found on the plasma membrane and on exosomes of various organelles. Reports on the function of Tspans during the early development of Xenopus have mainly focused on the expression of uroplakins in gametes. Although the roles of extracellular vesicles (EVs) including exosomes have been actively analyzed in cancer research, the contribution of EVs to early development is not well understood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It was reported that EV inhibition reduces cell migration in chick cranial neural crest development, but the role of Tspans in development remains largely unclear. Kuriyama and Tanaka (2023) analyzed expression patterns of 15 members of the Tspan family in X. laevis embryos, and classified them according to their expression patterns: "notochord," "brain," "eye," "cranial neural crest," "trunk neural crest," and "placode," implying that a combination of tspan genes may exert a specific role of EVs. They further performed cytological analysis of EVs generated with exogenously expressed Tspan proteins in the Xenopus embryo.…”
mentioning
confidence: 99%
“…It was reported that EV inhibition reduces cell migration in chick cranial neural crest development, but the role of Tspans in development remains largely unclear. Kuriyama and Tanaka (2023) analyzed expression patterns of 15 members of the Tspan family in X. laevis embryos, and classified them according to their expression patterns: "notochord," "brain," "eye," "cranial neural crest," "trunk neural crest," and "placode," implying that a combination of tspan genes may exert a specific role of EVs. They further performed cytological analysis of EVs generated with exogenously expressed Tspan proteins in the Xenopus embryo.…”
mentioning
confidence: 99%